A Novel High-Efficiency Multiple Output Single Input Step-Up Converter with Integration of Luo Network for Electric Vehicle Applications. (5th September 2022) - Ramu, Senthil Kumar; Balaganesh, Rajesh Kumar; Paramasivam, Suresh Kalichikadu; Muthusamy, Suresh; Panchal, Hitesh; Nuvvula, Ramakrishna S. S.; Kumar, Polamarasetty P; Khan, Baseem
Abstract : Concerns about pollution, climate change, limited fossil fuel supplies, and the desire to eliminate energy dependency have sparked a surge in interest in electric vehicles (EVs). EV requirements have resulted in a variety of difficulties and remedies in EV technology. One of them is the use of DC-DC converters to transfer the level of voltage from the battery in an EV to other needed voltage levels. An independent converter for each operating voltage might be used as a remedy. On the other hand, single input multiple output (SIMO) converters can be utilized to decrease costs, reduce switching loss, and thus enhance the system efficiency. In this paper, a nonisolated step-up converter with the integration of the Luo network is proposed for multiple outputs (24 V and 48 V). In electric vehicles, 48 V is utilized for battery backup, while 24 V is utilized for the horns, headlights, telematics, or the microcontroller. The experimental observations of a 36 V, 600 mA, 24 W prototype confirm the theoretic examination and demonstrate the advantages of the proposed converter over other multioutput converters. The STM microcontroller, based on an ARM cortex microprocessor, is linked into the Luo network for making pulses. The proposed converter achieves 94.2% efficiency at full power. The proposed converter's performance is evaluated through MATLAB/SIMULINK software, and the results are validated experimentally.